2017
DOI: 10.3390/su9030335
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Economic Growth: The Role of Foreign-Owned Banks in CESEE Countries

Abstract: This study focuses on the role of financial development in the economic growth of Central, Eastern and South-Eastern European (CESEE) countries in the post-communist era (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), which coincides with the opening up of financial markets to foreign investors and the global financial crisis. We investigate whether economic growth in CESEE countries has benefited from the presence of foreign-owned banks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 99 publications
5
29
0
8
Order By: Relevance
“…Also, financial sector development was significantly and positively related to IBs" stability. This result supports the result of Bongini et al (2017), and it is opposite from results of Growe et al (2014). While, financial crisis period, oil price volatility risk, and profitability of CBs have a negative impact, even though they have not a significant impact on financial stability of IBs.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Also, financial sector development was significantly and positively related to IBs" stability. This result supports the result of Bongini et al (2017), and it is opposite from results of Growe et al (2014). While, financial crisis period, oil price volatility risk, and profitability of CBs have a negative impact, even though they have not a significant impact on financial stability of IBs.…”
Section: Resultssupporting
confidence: 59%
“…Another variable that represents banking industry efficiency is financial sector development. Thus it may impact bank performance, as it is measured by the ratio of bank credit to the private sector divided by Gross Domestic Product (GDP) (Bongini, Iwanicz-Drozdowska, Smaga, & Witkowski, 2017), the financial sector development in some less developed countries, may enhance bank efficiency and performance. However, results from other studies indicated otherwise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then changed to be insignificant during the crisis period for the stability of both IBs and CBs but became negatively related to ZSC_CB. Results that positively related to financial stability supports result of Bongini et al (2017), and it is opposite from results of Growe et al (2014). While after crisis period, FSD is negatively related to stability of IBs and CBs, but it is significant at a 5% level of significance.…”
Section: Gls Estimationsmentioning
confidence: 56%
“…For instance, these studies allude that more significant development of financial sector could also create more competition, which may adversely impact the profitability of banks (Growe, DeBruine, Lee, & Maldonado, 2014). Financial sector development is measured by the ratio of bank credit to the private sector divided by GDP (Bongini, Iwanicz-Drozdowska, Smaga, & Witkowski, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analysis of scientific literature has shown that the problem of influence of foreign capital on state's financial and economic security requires additional research. Many scientists and bankers try to identify advantages and disadvantages of foreign capital involvement in the country's bank system (Heyets, 2006;Kornyliuk, 2012;Bongini, 2017), show pros and cons of foreign banks' activity (Chub, 2009;Levin, 1996), as well as determine the efficiency of the functioning of the country's bank system when foreign investors are engaged (Kolodiziev & Shvets, 2008;Nezhurin & Podchesova, 2013;Bruno, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%